The use of agencies by the Ministry of Internal Affairs of the Ukrainian SSR to control academic historical science in Soviet Ukraine (1953) - O. N. Yarmysh; V. A. Grechenko (Bulletin of Kharkiv National University of Internal Affairs)
One of the working methods of the state security bodies of the Ukrainian SSR, which were then part of the combined Ministry of Internal Affairs with the scientific intelligentsia, namely with the employees of the Institute of History of the Academy of Sciences of the Ukrainian SSR, was revealed. Through the agent, who worked in this structure, state security officials tried to influence the personnel of the Institute and the main areas of its scientific activity. The agent's report was summarized and thoroughly analyzed. In his reports, a description of the state of work on the main research of the Institute’s scientists was provided, with the corresponding assessments characteristic of the era of Stalinist dominance, and, as a rule, a negative description of the Institute’s leading scientists and managers. Attention is focused on several main aspects: the agent work of state security agencies among the scientific intelligentsia and the state and development of historical science in the republic at one of the turning points in its history, because it was in the middle of 1953 that the issue of the main directions of further political, ideological and social development of the state was resolved.